ChemInform Abstract: Gold‐Catalyzed Atom‐Economical Cascade Reactions of Alkynes for Ring Formation. Issue 18 (May 2015) - Ohno, Hiroaki; Oishi, Shinya; Fujii, Nobutaka
Abstract Review: development of gold‐catalyzed cascade reactions for atom‐economical synthesis f fused carbazoles, naphthalenes, dihydropyrazoles/indazoles and indoloquinoline s; 61 refs.